H-bonding vs non-h bonding in 100% pyrene methacrylate comb polymers:self assembly probed by tres and temperature dependent fluorescence - Kaushlendra, K.; Asha, S. K. (Journal of Physical Chemistry B, 2014)
The differences in self-organization behavior in novel 100% pyrene labeled comb methacrylate polymers probed as a function of their varied origins of excimer formation are presented. The different structural variations in the polymers included the presence or absence of hydrogen bonding interactions in the form of urethane linkages, short or long alkyl spacer segments separating the pyrene units from the polymer backbone and linear versus kinked urethane linkage. The effect of variable concentration and temperature on the chemical shift of the NH proton of the urethane linkage was probed using 1H NMR experiments conducted at temperatures varying from 25 to 70 °C at two different concentrations (2.5 and 25 mmol) in DMSO-d6 as solvent. The photophysical properties of the polymers in dilute DMF solutions were investigated by steady state emission, fluorescence decay studies, time-resolved emission spectra (TRES), and variable temperature emission studies. It was observed that the polymer poly(PBH) having a non-hydrogen-bondable ester linkage in the pendant chains formed an excimer completely via a static mechanism and the ground state aggregate species were not broken even at higher temperatures. The polymer poly(PIC) having a short hydrogen-bondable urethane linkage formed an excimer via a static as well as dynamic mechanism. The other hydrogen-bondable urethane methacrylate polymers having a linear linker poly(PHH) and kinked linker (PIHP) formed excimer mostly via a dynamic mechanism with a very small contribution from the static route. The TRES studies carried out for the polymers provided significant insight into the excimer formation mechanism in these polymers. The variable temperature fluorescence studies highlighted the differences in the H-bonded vs non-H-bonded polymer as a function of their excimer recovery upon cooling.